Subjective Well-Being Among Teenager in Banda Aceh - Fitria, Ida; Hafiza, Sarah; Rasyidin, Ulfah (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2023)
This study aims to determine the subjective well-being of adolescents in Banda Aceh. Adolescent well-being was measured by subjective well-being scales, which comprised with cognitive and affective aspects. A quantitative descriptive analysis approach was used in this study. The participants were 293 teenagers from various schools and universities that spread across Banda Aceh, both public and private. The data collection instruments used were the SWLS and SPANE scales. Results of this study indicate that, life satisfaction of adolescents in Banda Aceh majority was categorized in "quite satisfied" as much as 41.3%, followed by "satisfied" as much as 27.6%, and "very satisfied" as much as 12.3%, while the other 18.8% are categorized in “less satisfied” and “dissatisfied”. Further, the participants of this research experience positive emotions more than negative emotions, as indicated by SPANE scale that showed "very balanced" = 31.1%, "balanced" = 65.5%, "less balanced" = 3.4%. This research approved that adolescents in Banda Aceh tend to have more positive feelings than negative feelings. This study also illustrates a new perspective in revealing the condition of adolescents who tend to be good, which was previously revealed that adolescence tends to feel full of "storm and stress".Keywords: Positive Emotions; Negative Emotions; Life Satisfaction; Adolescents